CAVITATION SWIRL AT THE ENTRANCE OF CENTRIFUGAL PUMP - Predin, Andrej; Gregorc , Boštjan; Biluš, Ignacijo (Journal of Energy Technology, 2024)
The trend toward higher speed and power in order to achieve high performance characteristics has inevitably increased the potential for operating instabilities in modern pumps. Even in theabsence of cavitation and its complications, these phenomena can lead to performance loss and, in the worst cases, to structural failure. One of the major sources of instability in a centrifugal pump is, as mentioned, cavitation within the pump. Cavitation of a centrifugal pump is the result of insufficient net positive suction head and can occur within the entire range of operating conditions. Cavitation may cause three different and undesirable effects: (a) a drop in head and efficiency curves, (b) damage to the impeller by pitting and erosion, and (c) structural vibration [2] and resulting noise [1]. Therefore, the cavitation process must be prevented by all means. This paper deals with the influences of a simple motionless fourͲblade guiding device on the cavitating characteristics of radial pump. In the case of cavitating flow regimes, three distinct operating possibilities are known: (a) the stable regime, in which the majority of cavitating centrifugal pumps operate, (2) the unstable regime described as hydroͲdynamically induced cavitation surging, and (3) the transient regime, described as thermodynamically induced surging (2).
Keywords: cavitation; centrifugal pump; computational fluid dynamics